Non-suicidal Self-Injury in Adolescence: The Role of Shame, Self-Criticism and Fear of Self-Compassion - Xavier, Ana (2016)
Background: Non-suicidal self-injury (NSSI) is a serious and relatively prevalent problem in adolescence. Although several studies have identified risk factors for the aetiology and maintenance of NSSI, little is known about the impact of individual and contextual variables in such pervasive behaviors among adolescents. Objective: This paper aims to test whether specific internal traits characterized by shame, self-criticism and fear of self-compassion impact on NSSI, through their effect in daily peer hassles and depression. Methods: Participants are 782 adolescents with 12-18 years-old from middle and secondary schools (years of education’s mean = 9.46). This study has a cross-sectional design. Self-report measures include external shame, self-criticism, fear of self-compassion, daily peer hassles, depressive symptoms and NSSI. Results: External shame, hated self and fear of self-compassion indirectly predict NSSI, through their effect in daily peer hassles and depression. The most pathological form of self-criticism (hated self) is strongly associated with NSSI. Conclusions: These findings contribute to clarification of the paths through which the belief that one is seen negatively by others, the hostile self-to-self relationship and the inability to direct compassion for self may increase NSSI. Daily peer hassles and current depressive symptoms seem to play an important role in the association between internal traits and NSSI. Preventive and intervention actions for reducing NSSI in adolescence should address not only interpersonal difficulties but also self-to-self relationship.